2016
DOI: 10.1016/j.ces.2015.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Mixing of Newtonian and viscoelastic fluids using “butterfly” impellers

Abstract: The mixing of high viscosity and viscoelastic fluids may be performed in industry using a "butterfly" impeller, which has received scant attention. This paper describes the characterisation of these impellers using both Newtonian and viscoelastic (Boger) fluids with an identical base viscosity under laminar flow conditions in batch tanks without baffles. Measurements are made using two rotational speeds (N = 30 or 60 rpm) over a wide range of impeller to tank diameter ratios from 0.53 to 0.98.Particle Image Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Giesekus suggested alteration of m or m G is achieved. This number was used by other authors [15,20,21], e.g., to characterize the influence of elasticity in their stirred systems. In the following, a variant of this El reduced by constants is defined, which would result from the relation…”
Section: By Using the Elasticity Number Elmentioning
confidence: 99%
“…Giesekus suggested alteration of m or m G is achieved. This number was used by other authors [15,20,21], e.g., to characterize the influence of elasticity in their stirred systems. In the following, a variant of this El reduced by constants is defined, which would result from the relation…”
Section: By Using the Elasticity Number Elmentioning
confidence: 99%
“…Butterfly impellers, which are used to mix medium to highly viscous products, such as plasters, putties, adhesives and silicones, have also been characterized by means of PIV (Westerlins, 2016). Ramsay et al (2016) studied the mixing of glycerol and of two viscoelastic Boger fluids (that is, fluids with constant viscosity but with elastic properties) with butterfly impellers, and found that these impellers are energetically more efficient than conventional Rushton and pitched blade turbines. However, their mixing performance is lower for viscoelastic fluids, because the latter tend to rotate as a solid body.…”
Section: Introductionmentioning
confidence: 99%
“…However, those industries which employ processing of jams, inks, polymers and other viscous fluids result in mixing operations under laminar flow conditions in order to homogenize the product. In laminar flow conditions, the level of mixing is low which results in non-homogeneities in composition [1,2]. Mixing in food industries encounters many challenges in maintaining the homogeneity, consistency and enhancement of the texture of final products as they are processed under laminar conditions.…”
Section: Introductionmentioning
confidence: 99%